Analisis Implementasi Modern Dressing Hidrocolloid terhadap Peningkatan Integritas Kulit pada Anak Usia Sekolah dengan Dermatitis - Mauliza, Rizky; Harkensia , Linur Steffi; Sutrisna, Eka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to analyze the implementation of Modern Hydrocolloid Dressing to improve skin integrity in school-age children with dermatitis. The method used was quantitative with a pretest-posttest control group design. The results showed that the use of Modern Hydrocolloid Dressing significantly improved skin integrity in school-age children with dermatitis. In the treatment group, the average dermatitis score decreased from 1.84 (SD = 0.473) to 1.16 (SD = 0.624) with a p-value of 0.001 (p < 0.05). Meanwhile, no significant changes were found in the control group; the average score decreased by only 0.12 points (p = 0.185), with the majority of respondents remaining in the moderate category. This confirms that conventional dressings, or no intervention, are less effective than Modern Hydrocolloid Dressing. In conclusion, the use of Modern Hydrocolloid Dressing has been shown to significantly improve skin integrity in school-age children with dermatitis. Keywords: School-Age Dermatitis, Modern Hydrocolloid Dressing, Skin Integrity